(untitled) (Research, Society and Development, 2025)
Introduction: Obstetric violence has been recognized as a public health problem. The consequences of this dehumanizing scenario often include postpartum depression (PPD), since the multifactorial nature of this disorder possibly makes disrespect and abuse during childbirth some of its triggering factors. However, the relationship between these characteristics needs to be better clarified. This study aimed to synthesize and critically analyze the available evidence on the relationship between obstetric violence and the occurrence of puerperal depression. Methodology: An integrative literature review was carried out, guided by the recommendations of Mendes (2008). A bibliographic survey was conducted on the BVS platform and in the PUBMED, SciELO, LILACS and SCOPUS databases, using descriptors extracted from the DECS/MESH platform. Results: Twelve articles were selected for full analysis. Ten studies showed a link between obstetric violence and postpartum depression. Discussion: Pregnancy and the postpartum period are periods of repeated risk for psychiatric disorders and, when combined with violence and mistreatment, the incidence of postpartum depression (PPD) increases. PPD can also affect the child, impairing its development and bond with the mother. However, it is common for the professional not to identify himself as the aggressor, requiring a reformulation of obstetric care to reduce the negative impacts and promote a humanized delivery. Conclusion: Obstetric violence can be one of the main aggravating factors for the occurrence of postpartum depression (PPD).